1980
DOI: 10.1037/0022-0167.27.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Effects of counselor gender on perceived credibility.

Abstract: This report evaluates preference for counselor gender and perceived credibility of counselor in relation to the type of client concern. Four videotaped interview scripts, in which a male and a female portrayed counselors interacting with a client in two interview scripts each (vocational concern, child-rearing concern), were shown to 262 secondary school students who assessed counselor credibility. Although a strong Counselor Gender preference X Client Concern was evident, there was no significant difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…We were able to find four analogue adolescent treatment credibility studies that were from the 1980's (Atkinson & Schwartz, 1984;Bernstein & Figioli, 1983;Lee, Hallberg, Jones, & Haase, 1980;Littrell, Caffrey, & Hopper, 1987) and one actual treatment credibility study (Stein et al, 2001). Obviously, more research is needed in the youth mental health treatment literature to see if this is also an important common process factor in youth-therapist interactions.…”
Section: Therapist Credibility/ Persuasivenessmentioning
confidence: 99%
“…We were able to find four analogue adolescent treatment credibility studies that were from the 1980's (Atkinson & Schwartz, 1984;Bernstein & Figioli, 1983;Lee, Hallberg, Jones, & Haase, 1980;Littrell, Caffrey, & Hopper, 1987) and one actual treatment credibility study (Stein et al, 2001). Obviously, more research is needed in the youth mental health treatment literature to see if this is also an important common process factor in youth-therapist interactions.…”
Section: Therapist Credibility/ Persuasivenessmentioning
confidence: 99%
“…In particular, research by Yanico and Hardin (1985) and others (cf. Banikiotes & Merluzzi, 1981;Boulware & Holmes, 1970;Fuller, 1963;Lee, Hallberg, Jones, & Haase, 1980) has revealed that counseling processes associated with gender are often mediated by the types of personal problem discussed between clients and counselors (cf. Subich, 1983).…”
mentioning
confidence: 99%
“…The presenting problem of the client can also affect preference. Lee, Hallberg, Jones, and Haase (1980) provided evidence for preference based upon the presenting concern of the client. For example, male counselors were preferred for vocational concerns but female counselors were preferred for issues of child rearing.…”
Section: Gender Preferencementioning
confidence: 99%